Fluid Therapy and the Microcirculation in Health and Critical Illness - Cooper, Edward S.; Silverstein, Deborah C. (Frontiers in Veterinary Science, 2021)
Fluid selection and administration during shock is typically guided by consideration of macrovascular abnormalities and resuscitative targets (perfusion parameters, heart rate, blood pressure, cardiac output). However, the microcirculatory unit (comprised of arterioles, true capillaries, and venules) is vital for the effective delivery of oxygen and nutrients to cells and removal of waste products from the tissue beds. Given that the microcirculation is subject to both systemic and local control, there is potential for functional changes and impacts on tissue perfusion that are not reflected by macrocirculatory parameters. This chapter will present an overview of the structure, function and regulation of the microcirculation in health and shock states such as trauma, hemorrhage and sepsis. This will set the stage for consideration of how these microcirculatory characteristics, and the potential disconnect between micro- and macrovascular perfusion, may affect decisions related to acute fluid therapy (fluid type, amount and rate) and monitoring of resuscitative efforts. Available evidence for the impact of various fluids and resuscitative strategies on the microcirculation will also be reviewed.